Is determination of exercise intensities as percentages of VO2max or HRmax adequate? - Meyer, T.; Gabriel, H. H.; Kindermann, W. (Medicine & Science in Sports & Exercise, 1999)
Often exercise intensities are defined as percentages of maximal oxygen uptake (VO2max) or heart rate (HRmax). PURPOSE: The purpose of this investigation was to test the applicability of these criteria in comparison with the individual anaerobic threshold. METHODS: One progressive cycling test to exhaustion (initial stage 100 W, increment 50 W every 3 min) was analyzed in a group of 36 male cyclists and triathletes (24.9 +/- 5.5 yr; 71.6 +/- 5.7 kg; VO2max: 62.2 +/- 5.0 mL x min(-1) x kg(-1); individual anaerobic threshold = IAT: 3.64 +/- 0.41 W x kg(-1); HRmax: 188 +/- 8 min). Power output and lactate concentrations for 60 and 75% of VO2max as well as for 70 and 85% of HRmax were related to the IAT. RESULTS: There was no significant difference between the mean value of IAT (261 +/- 34 W, 2.92 +/- 0.65 mmol x L(-1)), 75% of VO2max (257 +/- 24 W, 2.84 +/-0.92 mmol x L(-1)), and 85% of HRmax (259 +/- 30 W, 2.98 +/- 0.87 mmol L(-1)). However, the percentages of the IAT ranged between 86 and 118% for 75% VO2max and 87 and 116% for 85% HRmax (corresponding lactate concentrations: 1.41-4.57 mmol x L(-1) and 1.25-4.93 mmol x L(-1), respectively). The mean values at 60% of VO2max (198 +/- 19 W, 1.55 +/- 0.67 mmol x L(-1)) and 70% of HRmax (180 +/- 27 W, 1.45 +/- 0.57 mmol x L(-1)) differed significantly (P < 0.0001) from the IAT and represented a wide range of intensities (66-91% and 53-85% of the IAT, 0.70-3.16 and 0.70-2.91 mmol x L(-1), respectively). CONCLUSIONS: In a moderately to highly endurance-trained group, the percentages of VO2max and HRmax vary considerably in relation to the IAT. As most physiological responses to exercise are intensity dependent, reliance on these parameters alone without considering the IAT is not sufficient.